AB0894 A Common VEGF -634G/C Polymorphism is Associated with Henoch-Schonlein Purpura Nephritis. (10th June 2014) - Zeng, H.; Xiong, X.
Abstract : Objectives: The purpose of this study was to evalulate the role of the single nucleotide polymorphism (SNP) –634 G/C at the 5'-untranslated region (UTR) of the vascular endothelial growth factor (VEGF) in the susceptibility to children with Henoch-Schonlein Purpura nephritis (HSPN) in the south of China. Methods: A case-control study was conducted in 100 children with Henoch-Schonlein Purpura (HSP) of Chinese Han population in the south of China. Patients were diagnosed according to proposed criteria. Patients (n=100) and ethnically matched controls (n=50) were genotyped for the VEGF -634G/C polymorphisms using PCR-RFLP technology. VEGF plasma levels were measured using an enzyme immunoassay. 100 patients included 50 patients with HSPN and 50 patients without HSPN. All patients were required to have had at least 6 month' follow-up. Results: No significant difference in the allele or genotype frequencies for the VEGF -634G/C polymorphism was observed between HSP patients without HSPN and controls. The VEGF -634 CC genotype and -634 C allele were increased in patients with HSPN compared with HSP patients without HSPN and healthy controls. The -634C allele was associated with susceptibility to HSPN. The -634G allele was a protective factor of HSPN. Furthermore, VEGF plasma levels were significantly higher in subjects with the CC genotype of the -634 G/C polymorphism than in those with the other genotypes. Conclusions: These data suggest that the VEGF-634C allele in the 5'UTR of the VEGF gene is a genetic risk factor in the development of nephritis in patients with HSP in the south of China. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5553